Financial Management Literacy and Training in Making Piggy Banks from Plastic Bottle Waste with Children in Lempuyang Village, Anjatan District, Indramayu Regency - Didik Himmawan; Laelatur Rizan (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
Managing money is one of the basic skills that everyone needs to have, and has even been recognized by the Ministry of Education and Culture as part of the National Literacy Movement. Managing money can also be done by saving. Saving is one of the character formations that is one of the habits that must be instilled from an early age. Saving from an early age can train children's ability to be responsible and become independent individuals which will be useful for their lives in the future. Of course, by saving, children themselves begin to learn to save. The purpose of this activity is to provide an understanding of the importance of financial management by saving for elementary school children, as well as to teach and hone the creativity that exists in students. The methods used during learning assistance are lectures, discussions and practices, this practice is carried out using plastic bottle waste media as piggy banks. Data analysis in this activity using pretests and posttests and tested using gain tests. The results of this activity, children in the Sukareja Gribig RT hamlet. 04 rw.03 become more aware of the importance of managing finances including how to save and plan a budget, foster children's creativity in making and utilizing plastic bottle waste so that it can be utilized, with this activity children also contribute to efforts to reduce plastic waste and preserve the environment. The obstacles encountered by children in Lempuyang village are the lack of knowledge of children about the importance of managing finances and saving, Lack of utilization of plastic bottle waste that can be utilized properly and has a selling value. The follow-up to this activity, children can implement saving at home with piggy banks that have been made during the implementation of the supporting program for the Islamic banking study program.